Transcriptional regulation of 5-HT(1A) receptor gene; Freud-2 a novel repressor of 5-HT(1A) receptor gene - Hadjighassem, Mahmoudreza (University of Ottawa (Canada), 2008)
The serotonin 1A receptor (5-HT1A) is expressed presynaptically on raphe neurons and works as an inhibitory autoreceptor. It is also expressed postsynaptically in limbic and cortical areas involved in mood and emotional regulation. Alteration in expression and function of 5-HT1A receptors is believed play an important role in etiopathology and treatment of mood disorders such as major depression. 5-HT1A receptor gene regulation was characterized. We have reported a dual repressor element that binds two complexes in non expressing 5-HT1A receptor cells (Freud-1/CC2D1B), but the identity of the second protein was unknown. We identified a mouse Freud-1 homologue (Freud-2/CC2D1B) that binds to the dual repressor element on the 5-HT1A promoter. We show that Freud-2 specifically reduces transcriptional activity of the post synaptic 5-HT1A receptor gene. Knocking down Freud-2 by specific siRNA unregulates expression of 5-HT1A. In addition, we extended our studies to identify and examine the human Freud-2. We show repressor function of Freud-2 in different human cell lines. Further studies on human normal post mortem brains using a specific anti-Freud-2 antibody reveal that Freud-2 is highly expressed in the nucleus of postsynaptic neurons in prefrontal cortex and hippocampus region in human and distributed in grey matter of these regions. We conclude that Freud-2 has a potential role in modulating mood and emotional response by altering the expression of postsynaptic 5-HT1A.
Keywords: Biology, Neuroscience.